A genetically engineered Fc-binding amphiphilic polypeptide for congregating antibodies in vivo. (1st April 2019) - Liu, Wen; Wong-Noonan, Stephanie; Pham, Ngoc B.; Pradhan, Isha; Spigelmyer, Amy; Funk, Riley; Nedzesky, Justin; Cohen, Henry; Gawalt, Ellen S.; Fan, Yong; Meng, Wilson S.
Graphical abstract: Abstract: We report herein an affinity-based hydrogel used in creating subcutaneous depots of antibodies in vivo . The biomaterials design centered on pG_EAK, a polypeptide we designed and expressed in E. coli . The sequence consists of a truncated protein G (pG) genetically fused with repeats of the amphiphilic sequence AEAEAKAK ("EAK"). Capture of IgG was demonstrated in vitro in gels prepared from admixing pG_EAK and EAK ("pG_EAK/EAK gel"). The binding affinities and kinetics of pG for IgG were recapitulated in the pG_EAK polypeptide. Injecting IgG antibodies formulated with pG_EAK/EAK gel into subcutaneous space resulted in retention of the antibodies at the site for at least six days, whereas only signal at background levels was detected in grafts injected with IgG formulated in saline or diffusion-driven gel. The local retention of IgG in pG_EAK/EAK gel was correlated with limited distribution of the antibody in liver, spleen and lymph nodes, in contrast to those injected with antibodies formulated in saline or non-Fc binding EAK gel. In addition, antibodies formulated with pG_EAK/EAK gel and injected in mouse footpads were found to retain at the site for 19 days. As a demonstration of potential bioengineering applications, thymic epithelial cells (TECs), the primary population of thymic stromal cells that are critical for the development of T-lymphocytes, were mixed with pG_EAK/EAK gel formulated with TEC-specific anti-EpCAM antibodies and injected subcutaneously into athymic nude mice. The injected TECs congregated into functional thymic units in vivo, supporting the development of both CD4+ and CD8+ T cells as well as Foxp3+ regulatory T cells in the mice. In conclusion, pG_EAK/EAK gel can be used to retain IgG locally in vivo, and can be tailored as scaffolds for controlling deposition of molecular and/or cellular therapeutics. Statement of significance: The unique concept of the work centers on the genetic fusion of an Fc-binding domain and a self-assembling domain into a single polypeptide. To our knowledge, such bi-functional peptide has not been reported in the literature. The impact of the work lies in the ability to display IgG antibodies and Fc-fusion proteins of any specificity. The data shown demonstrate the platform can be used to localize IgG in vivo, and can be tailored for controlling deposition of primary thymic epithelial cells (TECs). The results support a biomaterials-based strategy by which TECs can be delivered as functional units to support T-lymphocyte development in vivo . The platform described in the study may serve as an important tool for immune engineering.